A Virus Infecting Hibiscus rosa-sinensis Represents an Evolutionary Link Between Cileviruses and Higreviruses - Olmedo-Velarde, Alejandro; Hu, John; Melzer, Michael J. (Frontiers in Microbiology, 2021)
Hibiscus (Hibiscus spp.) are popular ornamental and landscape plants in Hawaii which are susceptible to foliar diseases caused by viruses belonging to the genera Cilevirus and Higrevirus (family Kitaviridae). In this study, a virus infecting H. rosa-sinensis plants displaying foliar symptoms consistent with infection by a kitavirus, including yellow chlorotic blotches with a green perimeter, was characterized. The genome consisted of two RNAs 8.4 and 4.4 kb in length, and was organized most similarly to cileviruses, but with important distinctions. These included the location of the p29 homolog as the 3′-terminal open reading frame (ORF) of RNA2 instead of its typical locus at the 3′-end of RNA1; the absence of a p15 homolog on RNA2 and the adjacent intergenic region which also harbors small putative ORFs of unknown function; and the presence of an ORF encoding a 10 kDa protein at the 3′-terminal end of RNA1 that was also found to be present in the hibiscus green spot virus 2 genome. Spherical particles approximately 55–65 nm in diameter were observed in infected leaf tissue, and viral RNA was detected by reverse-transcription PCR in individual mites collected from symptomatic plants tentatively identified as Brevipalpus yothersi. Although phylogenetic analyses placed this virus between the higrevirus and cilevirus clades, we propose the tentative taxonomic placement of this virus, designated hibiscus yellow blotch virus (HYBV), within the genus Cilevirus.